The influence of the gut microbiome on polycystic ovary syndrome - literature review - Cholewa, Małgorzata Maria; Zapała, Magdalena Alicja; Łapaj, Monika; Cichoń, Katarzyna; Kromer, Agata; Wilk, Joanna; Czarnota, Julia; Gawryś, Agnieszka; Chyćko, Małgorzata; Środoń, Agnieszka (Journal of Education, Health and Sport, 2023)
The intestinal microbiome is an integral part of our body, and a normal intestinal microflora allows the body to maintain homeostasis. Dysbiosis can contribute to the development of many cardiovascular diseases, can affect the development of cancer, gynecological diseases. Polycystic ovary syndrome affects many women of reproductive age and leads to a decrease in the quality of life of patients facing this problem. The main symptoms of PCOS are: menstrual disorders, problems with getting pregnant, skin problems (acne, hirsutism), obesity. The mainstay of treatment is hormonal medication, metformin. There are reports of supplementing drug therapy with diet, a healthy lifestyle. In recent years, there have been a number of studies looking for a relationship between the state of the intestinal microflora and polycystic ovary syndrome. In our work, we reviewed the available literature in the PuBMed database from 2019 to 2023 with key words on the studies related to our topic.